2020
DOI: 10.7589/2019-02-036
|View full text |Cite
|
Sign up to set email alerts
|

Low Serologic Prevalences Suggest Sporadic Infections of Hepatitis E Virus in Chamois (Rupicapra rupicapra) and Red Deer (Cervus elaphus) in the Italian Alps

Abstract: Hepatitis E virus (HEV) is a worldwide public health concern, with an increase in human autochthonous cases in Europe. Although domestic pigs and wild boar (Sus scrofa) are the main reservoirs of HEV, the constant expansion of wild ruminants increases the potential for HEV transmission. We investigated HEV infection in chamois (Rupicapra rupicapra) and red deer (Cervus elaphus) in the Italian Alps using an enzyme-linked immunosorbent assay (ELISA). We detected HEV antibodies from 2013 to 2015 in both host spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…Indeed, in our analysis, HEV molecular evidence was not obtained in any of the wild ruminants included in the screening. Furthermore, we found an overall low seroprevalence rate for HEV (3.5%; 4/115), confirming previous data collected during 2013-2015 surveillance from three distinct Italian Alpine regions [69], in which HEV antibodies were detected with rates of 1.2% (2/172) in chamois and 0.8% (2/254) in red deer. Accordingly, it could be hypothesized a limited role of these wild animals in maintaining HEV circulation, at least in the investigated geographical settings.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, in our analysis, HEV molecular evidence was not obtained in any of the wild ruminants included in the screening. Furthermore, we found an overall low seroprevalence rate for HEV (3.5%; 4/115), confirming previous data collected during 2013-2015 surveillance from three distinct Italian Alpine regions [69], in which HEV antibodies were detected with rates of 1.2% (2/172) in chamois and 0.8% (2/254) in red deer. Accordingly, it could be hypothesized a limited role of these wild animals in maintaining HEV circulation, at least in the investigated geographical settings.…”
Section: Discussionsupporting
confidence: 90%
“…However, higher values have been observed in red deer from Spain (10.4%, 101/968 to 12.85%, 9/70), Italy (13.9%, 35/251), and Sweden (7%, 1/14) [ 39 , 43 , 44 , 45 ]. The HEV seroprevalence in red deer appears to be generally low in Europe, as reported in Germany (rates of 2%, 2/100 and 3.3%, 2/61) [ 46 ], Belgium (1%, 2/189) [ 30 ], and Italy (0.8%, 2/254 to 2.6%, 1/38) [ 35 , 47 ]. All red deer studied in Poland (n = 118) and in Germany (n = 78) were seronegative [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, the contribution of suids to the circulation of HEV in Norway is probably moderate, suggesting that cervids could have a bigger role in the epidemiology of HEV in Norway. The circulation of HEV in red deer and chamois ( Rupicapra rupicapra ) in certain Alpine regions without suids has been described by Trogu et al [ 35 ]. The low seroprevalence rates found in muskoxen and red deer (5.9%, 6/102, and 4%, 7/177, respectively) indicate that they are possibly incidental HEV hosts in Norway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Italian wild boar populations, HEV infection is common, and the mean seroprevalence ranges from 4.9% [ 17 ] to 56.2% [ 18 ]. The infection in other wild animal species has been rarely investigated, but two studies conducted on red deer have confirmed the circulation of HEV-3 with seroprevalence values ranging from 1.2% [ 19 ] to 13.9% [ 20 ], and to a lesser extent (0.8%) also in chamois [ 19 ]. In the present case-control study, the seroprevalence of anti-IgG HEV antibodies in forestry workers (exposed group), in contact with wild animals and in a control group, was investigated, in order to evaluate the potential risk linked to professional activities.…”
Section: Introductionmentioning
confidence: 99%